The Relationship between the Size and the Invasion Depth of Tumors in Head and Neck Cutaneous Squamous Cell Carcinoma - Lee, Sam Yong; Hwang, Won Joo; Kim, Kyung Pil; Kim, Hong Min; Hwang, Jae Ha; Kim, Kwang Seog (Archives of Plastic Surgery, 2016)
Background Cutaneous squamous cell carcinoma (SCC), which occurs in keratinocytes of the epidermis and is the second most common skin cancer, has a more invasive growth pattern and higher potential to metastasize than basal cell carcinoma. Total excision of the primary tumor is the treatment of choice. For clear excision of the tumor, invasion depth is one of the most important factors. This study was conducted to clarify the relationship between the size and the invasion depth of cutaneous SCC.Methods Twenty-six cases were collected for this prospective study. Frozen biopsies were examined after complete resection of the tumor, followed by histological confirmation by pathological examination. The major and minor axis lengths of the tumor, the invasion depth, and the level of invasion were measured. Recurrence or metastasis was recorded through regular follow-up.Results The Pearson correlation coefficient was used for statistical analysis. Significant results were observed for the relationship between the major and minor axis lengths and the invasion depth of the tumor (0.747, 0.773). No cases of recurrence or metastasis were observed.Conclusions In head and neck cutaneous SCC, the invasion depth of the tumor is closely related to the major and minor axis lengths of the tumor. Therefore, the invasion depth of the tumor can be estimated by measuring the size of the tumor, and a standard vertical safety margin for head and neck cutaneous SCC can be established, which could be helpful in the development of a preoperative reconstruction plan.
Keywords: Carcinoma; Epithelial cells; Skin neoplasms; Keratinocytes